Ocean acidification impairs growth and induces oxidative stress in the macroalgae Ulva fasciata and Petalonia fascia - de Freitas, Fernanda Ribeiro [UNESP]; Barboza, Letícia Viana [UNESP]; Kühl, Vitória Caroline Pereira [UNESP]; Castro, Ítalo Braga; Lima Neto, Milton Costa [UNESP] (Elsevier, 2025)
Ocean acidification (OA), driven by increasing anthropogenic CO2 uptake, poses a significant threat to marine ecosystems; understanding the physiological responses of key primary producers like macroalgae is crucial for predicting ecological consequences. This study investigated the impacts of OA on the green alga Ulva fasciata and the brown alga Petalonia fascia. We aimed to determine the effects of decreased pH on their growth, photosynthetic performance, biochemical composition, and oxidative stress responses. Algae were exposed for 15 days to three pH levels: 8.2, 7.4 and 6.5. We measured multiple parameters including relative growth rate, chlorophyll a fluorescence parameters, H2O2 content, lipid peroxidation, and activities of superoxide dismutase and catalase. Results showed that decreasing pH reduced relative growth rate in both species, with reductions of up to 58 % in U. fasciata and 64 % in P. fascia at pH 6.5. Photosynthetic efficiency and chlorophyll content also declined significantly under lower pH, while non-photochemical quenching generally increased. Both species exhibited increased membrane damage, H2O2 content, and TBARS levels at lower pH, indicative of oxidative stress. Antioxidant enzyme activities were significantly modulated, with significant interactions between pH and species observed for most parameters, highlighting differential physiological adjustments. These findings indicate that both Ulva fasciata and Petalonia fascia are susceptible to detrimental effects from simulated OA, suggesting potential shifts in the competitive balance and structure of intertidal macroalgal communities.